1983
DOI: 10.1090/s0002-9947-1983-0704607-8
|View full text |Cite
|
Sign up to set email alerts
|

Stability criteria for Volterra equations

Abstract: Abstract. We consider a system of integro-differential equations of the form (1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 8 publications
4
24
0
Order By: Relevance
“…If a > Z 1 0 k(s) ds; (1.2) it is proved in [7] that the following all hold. If a > Z 1 0 k(s) ds; (1.2) it is proved in [7] that the following all hold.…”
Section: Introductionmentioning
confidence: 99%
“…If a > Z 1 0 k(s) ds; (1.2) it is proved in [7] that the following all hold. If a > Z 1 0 k(s) ds; (1.2) it is proved in [7] that the following all hold.…”
Section: Introductionmentioning
confidence: 99%
“…Brauer [6] showed that the solution could not be stable if ∞ 0 k(s)ds > a, Burton and Mahfoud [7] proved the zero solution is asymptotically stable if ∞ 0 k(s)ds < a, Kordonis and Philos [8] discussed the stability of the solution under condition ∞ 0 k(s)ds = a. Therefore, a necessary condition for lim t→∞ x(t) = 0 for all solutions is that ∞ 0 k(s)ds ≤ a.…”
Section: K(t − S)x(s)dsmentioning
confidence: 99%
“…Nonlinear integro-differential equations have been widely studied by researchers due to its wide applications in biology, ecology, medicine, physics, engineering and other scientific areas, (see [3], [5], [20] and reference therein). In recent years, qualitative properties of solutions such as stability, instability, boundedness, existence etc.…”
Section: Introductionmentioning
confidence: 99%